Shakespeare on the couch : on behalf of the United Kingdom Council for Psychotherapy - Jacobs, Michael, 1941- (Karnac Books, 2008)
Drawing upon a vast literature in psychoanalytic journals and either upon Shakespeare's characters themselves or alluding to those characters in the course of other topics, this book discusses eight of Shakespeare's plays and the relationships between the main characters in them.
Keywords: Shakespeare, William, -- 1564-1616 -- Knowledge -- Psychology.; Shakespeare, William, -- 1564-1616 -- Characters.; Shakespeare, William, -- 1564-1616; Psychoanalysis and literature -- England.; Drama -- Psychological aspects.; Psychology in literature.; Psychanalyse et littérature -- Angleterre.; Théâtre (Genre littéraire) -- Aspect psychologique.; Psychologie dans la littérature.; LITERARY CRITICISM -- Shakespeare.; DRAMA -- Shakespeare.; Psychoanalysis.; Characters and characteristics; Drama -- Psychological aspects; Psychoanalysis and literature; Psychology; Psychology in literature; England